2019
DOI: 10.1055/a-0752-0514
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for remaining liver injury in patients with virological elimination of chronic hepatitis C

Abstract: Background and aims Disease activity, but also demographics, lifestyle, and comorbidities, may influence alanine aminotransferase (ALT) levels in hepatitis C virus (HCV)-infected patients. Direct-acting antiviral agents (DAA) achieve virological cure in > 90 % of patients, regardless of HCV genotype and fibrosis stage. This allows assessing determinants for ALT levels before and after elimination of HCV. Methods Our prospective cohort included HCV- and HIV/HCV-infected patients treated with DAA at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…Our findings align well with smaller cohort studies from Spain (n = 1112) and Germany (n = 834), in which 11.7% or 10% had persistently elevated ALT . We had previously reported up to 15% with elevated ALT (221/1477) after DAA therapy from a different outpatient cohort of HCV‐infected patients . If the stricter AASLD criteria for normal ALT are applied, 38.5% of the patients in our current study (1906/4946) had persistently abnormal ALT despite DAA therapy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings align well with smaller cohort studies from Spain (n = 1112) and Germany (n = 834), in which 11.7% or 10% had persistently elevated ALT . We had previously reported up to 15% with elevated ALT (221/1477) after DAA therapy from a different outpatient cohort of HCV‐infected patients . If the stricter AASLD criteria for normal ALT are applied, 38.5% of the patients in our current study (1906/4946) had persistently abnormal ALT despite DAA therapy.…”
Section: Discussionsupporting
confidence: 90%
“…7,8 We had previously reported up to 15% with elevated ALT (221/1477) after DAA therapy from a different outpatient cohort of HCV-infected patients. 9 If the stricter AASLD criteria for 8 Our study confirms and extends these findings, by pointing towards obesity/NAFLD, alcoholism and cirrhosis as the main relevant co-factors in HCV-infected patients. However, we need to acknowledge that steatosis was assessed by ultrasound in our registry, as done in similar prior studies with IFN-based therapies, 16 but not by controlled attenuation parameter (CAP), magnetic resonance spectroscopy (MRS), MRI-Proton density fat fraction (MRI-PDFF) or histology, which would have been more accurate and more quantitative to assess steatosis.…”
Section: Risk Factors For Persistently Elevated Liver Tests After Dsupporting
confidence: 81%
See 2 more Smart Citations
“…Noureddin et al 51 found that 47.5% of the patients who achieved an SVR had NAFLD, with some patients, having clinically significant fibrosis despite presenting with normal liver enzymes. In a recent study from Mauss et al, 52 male sex, advanced liver disease, and obesity were associated with persistence of ALT elevations in patients with SVR, suggesting fatty liver disease could be a potential cofactor of fibrosis progression. These authors therefore recommend to search for steatosis after SVR and continue lifelong surveillance in patients with documented fatty liver disease.…”
Section: Recommendations and Expert Opinionmentioning
confidence: 93%